Early Recurrence After Hepatectomy for Colorectal Liver Metastases: What Optimal Definition and What Predictive Factors?. (28th April 2016) - Imai, Katsunori; Allard, Marc‐Antoine; Benitez, Carlos Castro; Vibert, Eric; Sa Cunha, Antonio; Cherqui, Daniel; Castaing, Denis; Bismuth, Henri; Baba, Hideo; Adam, René
Abstract : Background: The purpose of this study was to determine the optimal definition and elucidate the predictive factors of early recurrence after surgery for colorectal liver metastases (CRLM). Methods: Among 987 patients who underwent curative surgery for CRLM from 1990 to 2012, 846 with a minimum follow‐up period of 24 months were eligible for this study. The minimum p value approach of survival after initial recurrence was used to determine the optimal cutoff for the definition of early recurrence. The predictive factors of early recurrence and prognostic factors of survival were analyzed. Results: For 667 patients (79%) who developed recurrence, the optimal cutoff point of early recurrence was determined to be 8 months after surgery. The impact of early recurrence on survival was demonstrated mainly in patients who received preoperative chemotherapy. Among the 691 patients who received preoperative chemotherapy, recurrence was observed in 562 (81%), and survival in patients with early recurrence was significantly worse than in those with late recurrence (5‐year survival 18.5% vs. 53.4%, p < .0001). Multivariate logistic analysis identified age ≤57 years ( p = .0022), >1 chemotherapy line ( p = .03), disease progression during last‐line chemotherapy ( p = .024), >3 tumors ( p = .0014), and carbohydrate antigen 19‐9 >60 U/mL ( p = .0003) as independent predictors of early recurrence. Salvage surgery for recurrence significantly improved survival, even in patients with early recurrence. Conclusion: The optimal cutoff point of early recurrence was determined to be 8 months. The preoperative prediction of early recurrence is possible and crucial for designing effective perioperative chemotherapy regimens. Implications for Practice: In this study, the optimal cutoff point of early recurrence was determined to be 8 months after surgery based on the minimum p value approach, and its prognostic impact was demonstrated mainly in patients who received preoperative chemotherapy. Five factors, including age, number of preoperative chemotherapy lines, response to last‐line chemotherapy, number of tumors, and carbohydrate antigen 19‐9 concentrations, were identified as predictors of early recurrence. Salvage surgery for recurrence significantly improved survival, even in patients with early recurrence. For better selection of patients who could truly benefit from surgery and should also receive strong postoperative chemotherapy, the accurate preoperative prediction of early recurrence is crucial. Abstract : To define and predict early recurrence after surgery, the authors examined 987 patients who underwent curative surgery for colorectal liver metastases. The optimal cutoff point of early recurrence was 8 months after surgery. Age, number of preoperative chemotherapy lines, response to last‐line chemotherapy, number of tumors, and carbohydrate antigen 19‐9 concentrations were identified as predictors of early recurrence. Salvage surgery significantly improved survival.